Measuring KVK-led Fisheries Extension Efforts in Haryana and Punjab: Insights and Interventions - Naila Majid Bhat,; Pachampalayam Shanmugam Ananthan,; Kuppusamy Ponnusamy,; Ashish Santosh Murai,; Shivaji Dadabhau Argade,; Neha Wajahat Qureshi,; Periyasamy Seenivasan, (Indian Journal of Extension Education, 2023)
KVKs have proved to be dynamic tools for agricultural development but their role and potential contribution for fisheries development is less known. This study, conducted in 2023, quantifies fisheries extension efforts of all 22 KVKs in Punjab and 19 KVKs in Haryana. The study relied on secondary data sourced from annual reports of ATARI-Ludhiana, ATARI-Jodhpur, ICAR-KVK portal, individual KVK websites as well as primary data collected from KVK-SMS in all districts using a structured online survey, besides field visits to few KVKs. A novel methodology, the KVK-Fisheries Extension Intensity Index (FEII) consisting of 5 dimensions (human resource, infrastructure, budget, fisheries extension activities, and digital outreach), was used to quantify the KVKs’ extension effort. The average FEI scores were 33% for Haryana KVKs and 36% for Punjab KVKs with none of the 41 KVKs having high FEI (>66%), clearly indicating inadequate attention to fisheries by KVKs. Nearly two-thirds of KVKs in Punjab (68%) and in Haryana (58%) had moderate FEI scores. The absence of fisheries SMS and fisheries infrastructure in all, but 5 KVKs in the two states were primary reasons for poor extension effort which needs speedy redressal.